A Stunting and Periodontal Disease - Maulani, Chaerita; Mustaqimah, Dewi Nurul; Priyadharsini, Sonya; Zakki, Muhamad (Lembaga Penelitian Universitas YARSI, 2023)
Background: Stunting is a condition where a child's height is insufficient for their age. Stunting in children under the age of five, which can be caused by chronic malnutrition, poses a danger of death. Objective: Stunting can have an impact on dental and oral health by increasing the risk for early childhood caries and delaying tooth eruption, also reducing the number of permanent teeth. Conversely, stunting may be impacted by poor dental health. Literature Study: Periodontal disease can have impact on pregnant women’s fetal growth such as premature birth and low birth weight babies both directly and indirectly. Subsequently, premature babies can increase the risk of stunting. Discussion: One of the stunting behind mechanisms was the discovery of differences in bacterial variations between stunted and normal children. Oropharyngeal bacteria, such as Porphyromonas gingivalis usually found in severe periodontitis, were detected in pregnant women which is likely to disrupt the host's immune homeostasis. Disorders in pregnant women can interfere with the process of tooth development in the fetus. Conclusion: Periodontal therapy in for periodontitis expecting mother, should have decrease the risk of adverse effect of pregnancy such as premature birth and low birth weight, and decrease the risk of having stunting children.